Environmental design load for the line force of a point-absorber wave energy converter. (November 2022) - Shahroozi, Zahra; Göteman, Malin; Nilsson, Erik; Engström, Jens
Abstract: To ensure a reliable operation over the life time of wave energy converters (WECs), a number of load cases need to be considered according to international standards for marine structures to determine an optimal design. This paper outlines the procedure of obtaining an environmental design load for the line force of a 1:30 scaled point-absorber WEC using an environmental contour with a 50-year return period for the Dowsing site in the North Sea. To obtain the response of the WEC during extreme conditions, a numerical WEC-Sim model is developed and calibrated with experimental wave tank tests to augment the data required for such design load analysis. The design load for the line force is estimated based on the full long-term extreme response computed from the full sea state approach by considering 180, 360, and 720 sea state samples as well as the contour approach for the sea state that gives the most extreme response. Further, a probabilistic approach is used to quantify the probability of failure for a critical mechanical component of the system such as shackle. The result shows that the numerical WEC-Sim model is able to sufficiently replicate the real response of the system during extreme irregular waves. The Bayesian theory with Monte-Carlo algorithm is found to be an excellent tool for identifying the degree of belief in the statistical models used for the short-term extreme response analysis. Considering the ultimate limit state, the design load for the 1:30 scaled system is calculated as 670.95 N (i.e. 18.11 MN for a full-scale system) after applying the partial load safety factor of 1.35 on the full long-term extreme response of the system for the 9.1 years return period (i.e. 50 years in a full-scale model). Highlights: Design load derivation using augmented data from a calibrated WEC-Sim model Different statistical approaches to calculate the system's short-term extreme response Discussing the deterministic and probabilistic failure analysis of shackle